Determinants Of Pulmonary Tuberculosis Patients' Cure In The Working Area Of Sei Agul Health Center, Medan West District, Medan City - Agnes Agnes; Maya Sari Mutia; Chrismis Novalinda Ginting (CV. Inara, 2023)
Tuberculosis is an infectious disease caused by the bacterium Mycobacterium tuberculosis, this bacterium usually attacks the lungs, but TB bacteria can attack any part of the body such as the kidneys, spine and brain. TB is one of the top 10 causes of death and the main killer of HIV sufferers worldwide. Based on WHO's 2018 Global Truberculosis Report, the incidence of tuberculosis in Indonesia in 2018 increased by 420,994 cases compared to the number of cases in 2017 of 360,565 cases and 2016 of 330,910 cases. According to gender, the number of cases in men is higher than in women, namely 1.4 times compared to women in each province throughout Indonesia.Methods: The study used a quantitative approach with an analytic observational type with a cross-sectional research design. Research results: motivation variables with significant values (0.000), medical history (0.005), knowledge (0.04), socioeconomic conditions (0.035) and education (0.022) have a relationship to the recovery of TB patients. While other variables are not related to the recovery of TB patients.